Centimeter-long and large-scale micropatterns of reduced graphene oxide films : fabrication and sensing applications - He, Qiyuan (2012)
Recently, the field-effect transistors (FETs) with graphene as the conducting channels have been used as a promising chemical and biological sensors. However, the lack of low cost and reliable and large-scale preparation of graphene films limits their applications. In this contribution, we report the fabrication of centimeter-long, ultrathin (1−3 nm), and electrically continuous micropatterns of highly uniform parallel arrays of reduced graphene oxide (rGO) films on various substrates including the flexible polyethylene terephthalate (PET) films by using the micromolding in capillary method. Compared to other methods for the fabrication of graphene patterns, our method is fast, facile, and substrate independent. In addition, we demonstrate that the nanoelectronic FETs based on our rGO patterns are able to label-freely detect the hormonal catecholamine molecules and their dynamic secretion from living cells.